Fluxogram for the management of the elderly with altered deglutition after cerebrovascular accident (Research, Society and Development, 2021)
Objective: To build a flowchart for the management of elderly people with swallowing disorders after stroke. Methods: Methodological study carried out in three stages: carrying out an integrative literature review; evaluation of 38 medical records about sociodemographic and clinical variables and the prevalence of swallowing disorders in elderly people after a stroke; and construction of a flowchart for the management of elderly people with swallowing disorders after a stroke, based on the first two steps. Results: The flow starts with the reception of the elderly person after a stroke in Primary Health Care, where they will be evaluated by a health professional. When checking changes in swallowing, the elderly will be referred for treatment with a physiotherapist and speech therapist or nutritionist, psychologist and speech therapist, according to pulmonary or nutritional and dietary changes, respectively. Conclusion: The flowchart helps health professionals in referring the elderly with this condition, providing adequate treatment by the multidisciplinary team.